2010
DOI: 10.1002/agr.20239
|View full text |Cite
|
Sign up to set email alerts
|

Product and process innovation in the Italian food industry

Abstract: The driving factors of innovation in the Italian food sector could be identified either in internal and in external dynamics. On one hand, the responses to the competition with new actors coming from emerging countries and the reaction to high-tech products demand evolution. On the other hand, endogenous dynamics appear to become more important for the strategic behaviour of the firms: a higher qualification of the human capital, a more clear orientation for high quality products, organization changes, and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
3
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 31 publications
10
166
3
8
Order By: Relevance
“…It is an unbeatable strategy' (M6). This result concurred with those of earlier studies (Capitanio et al, 2010;Lülfs-Baden et al, 2008), indicating that maintaining high product quality is one of the most effective strategies for creating differentiated value.…”
Section: Production Managementsupporting
confidence: 83%
See 1 more Smart Citation
“…It is an unbeatable strategy' (M6). This result concurred with those of earlier studies (Capitanio et al, 2010;Lülfs-Baden et al, 2008), indicating that maintaining high product quality is one of the most effective strategies for creating differentiated value.…”
Section: Production Managementsupporting
confidence: 83%
“…Russo, Cardillo, and Perito (2003) emphasised the critical roles of R&D investment and the risk of failure in product-innovation strategies. Capitanio, Coppola, and Pascucci (2010) suggested that the capacity to build relationships in product markets is the determinant of product innovation, and that the territorial context determines the relevance of each driving factor of innovation. Liu, Kemp, Jongsma, Huang, Dons, and Omta (2014) further argued that integrative capabilities play a crucial role in innovation novelty, which enhances product superiority, and in improving functional capabilities and gaining market potential.…”
Section: Internal Environmentmentioning
confidence: 99%
“…The second one, less used in OI literature, is process innovation. We also selected this measure because, as stressed before, previous studies have shown that FnB firms tend to innovate more in processes than in products (Capitanio et al, 2010). The third one relates to product novelty level, which we define as the percentage of newto-market products (radical), versus the percentage of products that are only new to the firm (incremental).…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…Innovation performance is identified as key factor of competitiveness (Capitanio et al, 2010;Grunert et al, 2005). Innovation is even more relevant in the context of the Hungarian food chain, a sector that has traditionally been internationally oriented but that also suffers from the legacy of former communist rule in which quality and innovative content of products and services was not a priority.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Notwithstanding that the Central-European countries have got some cost advantages compared to the West-European ones -which are mainly due to some foreign direct investments -they hardly can show up these pros at global level. Therefor our main concern should concentrate towards the quality and innovation issues, which underpin and determine the sustainable competitiveness on the long run (Capitanio et al, 2010;Grunert et al, 2005). In the recent debates researchers concatenate the regional differences in economic performance with the differences in innovation achievements (Abreu et al, 2008;Hansen and Winther, 2011).…”
Section: Introductionmentioning
confidence: 99%